2012
DOI: 10.1002/jhm.1955
|View full text |Cite
|
Sign up to set email alerts
|

Does sepsis treatment differ between primary and overflow intensive care units?

Abstract: BACKGROUND:Sepsis is a major cause of death in hospitalized patients. Early goal‐directed therapy is the standard of care. When primary intensive care units (ICUs) are full, sepsis patients are cared for in overflow ICUs.OBJECTIVE:To determine if process‐of‐care measures in the care of sepsis patients differed between primary and overflow ICUs at our institution.DESIGN:We conducted a retrospective study of all adult patients admitted with sepsis between July 2009 and February 2010 to either the primary ICU or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Another smaller study suggested that outcome differences may have occurred because of reduced compliance with HU care guidelines (e.g., deep venous thrombosis and gastrointestinal prophylaxis) in the boarding unit. 18 In our study, mortality tended to be 24% greater in the BUDF than in the HU ( p = 0.69).…”
Section: Discussionsupporting
confidence: 41%
“…Another smaller study suggested that outcome differences may have occurred because of reduced compliance with HU care guidelines (e.g., deep venous thrombosis and gastrointestinal prophylaxis) in the boarding unit. 18 In our study, mortality tended to be 24% greater in the BUDF than in the HU ( p = 0.69).…”
Section: Discussionsupporting
confidence: 41%
“…Bedspacing has been shown to be associated with worse outcomes among several patient populations. For example, critically ill patients who “board” in emergency departments (EDs) awaiting intensive care unit (ICU) beds or are bedspaced to alternate ICUs (eg, a medical patient admitted to a surgical ICU), may experience worse clinical outcomes (eg, prolonged hospital length of stay [LOS] and increased ICU and in-hospital mortality) and care inefficiencies 4–7…”
Section: Introductionmentioning
confidence: 99%
“…[2] Early goal-directed therapy is the standard of care. [5] Sepsis is a complex condition characterized by the simultaneous activation of inflammation and coagulation in response to microbial agents. Today, sepsis is a severe multisystem disease with difficult treatments.…”
Section: Discussionmentioning
confidence: 99%